New Generation Learning: Redefining Education in a Digital World - Pant, Yashodhara; Shiwakoti, Rabindra (NPRC Journal of Multidisciplinary Research, 2025)
The rapid expansion of digital technologies has instigated a paradigm shift in education, ushering in New Generation Learning, which utilizes technology to create more active, student-centered, and inclusive learning environments. This study presents a review of the transition from traditional to digital education, highlighting essential pedagogical practices such as differentiation, meaningful feedback, and the integration of digital tools to track curriculum progression. The paper explores the opportunities offered by e-learning platforms, blended learning, and emerging technologies like AI, VR, and AR, while also addressing challenges such as the digital divide, equitable access, and the ongoing need for professional development for educators. Employing a mixed-methods approach, the research collects qualitative data from interviews, classroom observations, and focus group discussions, alongside quantitative survey data that assess the effectiveness of active digital learning pedagogy.The study investigates student engagement, learning outcomes, and key success factors and barriers to implementation. The research has implications for curricular reform, assessment practices, and teacher training, urging a comprehensive overhaul of the education system to meet the demands of 21st-century learning. The findings emphasize the importance of collaboration, innovation, and digital literacy in preparing students for an interconnected, multicultural world. The study also calls for continued research, global collaboration, and evidence-based policy initiatives to ensure equitable access and maximize the potential of digital education.